Comparative analysis of logical acquisition using Wondershare Dr. Fone, MOBILedit Forensic, and FonePaw on android phones / Nuraimi Farhana Salimi, Nor Bakiah Abd Warif and Nor-Syahidatul N Ismail - Salimi, Nuraimi Farhana; Abd Warif, Nor Bakiah; N Ismail, Nor Syahidatul (UiTM Press, 2022)
The increasing number of mobile phone usage in storing confidential information, such as mobile online transactions has led to the growing number of research in mobile forensic. There are lot of crimes may happen through mobile phones, such as smishing, bluejacking, and malware attacks. Mobile forensic is a way of collecting any digital evidence on the mobile phone. Logical acquisition is one of the methods for mobile forensic. The methodology for logical acquisition consists of identification, isolation, acquisition, analysis, and documentation. This research aims to study, perform and analyze logical acquisition using Wondershare Dr. Fone for Android, MOBILedit Forensic, and FonePaw for Android in Android-based phones which are Oppo F9 and Samsung S7 Edge. The analysis is based on percentage of capability and time taken for each tested mobile forensic tool on the two selected Android phones. The results show that FonePaw for Android gets the highest average capability (97%) with the shortest time while MOBILedit Forensic obtains the lowest average capability (74%) with the longest time taken. This research may help the forensic investigators team to determine the suitability of mobile forensic tools with Android phones based on the Android features and type of files.